STRATEGI INTERNALISASI NILAI-NILAI MODERASI BERAGAMA SEBAGAI UPAYA PREVENTIF TERHADAP PEMAHAMAN RADIKALISME SISWA DI MADRASAH BERBASIS PESANTREN - Jazilurrahman; Miftahus Salam; Badrul Mudarris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the Strategies for Internalizing Religious Moderation Values as a Preventive Effort against Students’ Radicalism Understanding in Pesantren-Based Madrasahs in Islamic elementary education. Conducted at Madrasah Ibtidaiyah (MI) Syamsul Jinan Sumberjo Besuki, a pesantren-based school in a multicultural environment, the research adopts a qualitative case study approach. Data were collected through observation, in-depth interviews, and document analysis involving school leaders, Islamic education teachers, and students in grades 4, 5, and 6. Findings reveal that key values such as tasamuh (tolerance), tawassuth (moderation), i’tidal (balance), and muwathanah (civic responsibility) are systematically embedded in formal learning, religious practices, and school culture. Teachers and principals play vital roles as role models and facilitators who promote inclusive dialogue and critical thinking. Contextual teaching methods—such as open discussion, case studies, and reflective practice—help students internalize these values beyond theoretical understanding. Extracurricular activities further support character formation by encouraging cooperation, leadership, and respect for diversity. However, implementation is challenged by the absence of specific instructional materials, limited teacher training in diversity education, and the influence of unregulated digital content that may expose students to radical narratives. The study concludes that MI Syamsul Jinan serves as a practical model of how pesantren-based education can integrate religious moderation to foster tolerant and peaceful generations.